Prevalence of Thermophilic Campylobacter in Cattle Production at Slaughterhouse Level in France and Link Between C. jejuni Bovine Strains and Campylobacteriosis - Thépault, Amandine; Poezevara, Typhaine; Quesne, Ségolène; Rose, Valérie; Chemaly, Marianne; Rivoal, Katell (Frontiers in Microbiology, 2018)
Campylobacter is the leading cause of bacterial gastroenteritis in industrialized countries, with poultry reservoir as the main source of infection. Nevertheless, a recent study on source attribution showed that cattle could be a source of human contamination in France (Thépault et al. 2017). However, few data are available on thermophilic Campylobacter epidemiology in cattle in France. The aim of this study is to collect new data of thermophilic Campylobacter prevalence in these animals and to subtype C. jejuni isolates to assess the potential implication of cattle in campylobacteriosis. A 6-month survey was carried out in one of the largest European slaughterhouse of cattle. Based on a statistical representative sampling plan, 959 intestinal content samples (483 adult cattle and 476 calves) were collected. An adapted version of the ISO 10272 standard and Maldi-Tof were used for detection and speciation of thermophilic Campylobacter isolates. Within more than 2000 thermophilic Campylobacter isolates collected, a selection of 649 C. jejuni isolates was typed with Comparative Genomic Fingerprinting (CGF40) and a subset of 77 isolates was typed using Multilocus Sequence Typing (MLST). Simultaneously, clinical isolates occurred in France were genotyped. Prevalence of thermophilic Campylobacter in the global cattle population was 69.1% (CI95% = 66.1, 72.1) at slaughterhouse level. In adult cattle, the prevalence was 39.3 %, while 99.4% of calves were contaminated, and C. jejuni was the most prevalent species with prevalence of 37.3% and 98.5%, respectively and a higher genetic diversity in adult cattle. The prevalence of C. coli was lower with 3% in adult cattle and 12.5% in calves. MLST and CGF40 genotyping did not showed a high number of clusters within cattle isolates but the predominance of few clusters accounted for a large part of the population (CC-21, CC-61, CC-48, and CC-257). By comparison with clinical genotypes, genetic diversity was significantly lower in cattle. Moreover, significant overlap was observed between genotypes from both origins, with 3 of the 4 main cattle clusters present in human isolates. This study provides new insights on the epidemiology of thermophilic Campylobacter and C. jejuni in cattle production in France and their potential implication in human infection.